Tinjauan Yuridis UU Cipta Kerja Terhadap Pengupahan Yang Layak Era Pandemi Covid-19 - Eva Maya Sari; Gracia Tirta Immanuella; Ariani Sitanggang; Satria Ariayudha Widiatmoko; Laga Sugiarto (Jurnal Hukum dan Sosial Politik, 2023)
The legalizing of the work act sparked deep-rooted controversy in society, even since it was first proposed by the President. This situation is highly reasonable, especially with new society conditions emerging from the covid-19 pandemic, misunderstandings are natural and disagreements are easy. The copyright law was hasty as it revised dozens of existing laws. Omnibus law appeared on President Joko Widodo's proposal on his inaugural address to the people's assembly on October 20, 2019. The President proposed omnibus law to have overlapping regulations eliminated. The government has also expressed hope with the growing number of pollutive Omnibus Laws in the public and has also attracted foreign investors to invest in Indonesia. Omnibus law has generated controversy in society as it overcomes most of the previous legislation with the new one. This new act. Omnibus law provided an easier passage, as regulations and permits impeded increased construction.